Equality beyond debate John Dewey's pragmatic idea of democracy - Jackson, Jeff (Cambridge University Press, 2018)
Introduction -- The democratic individual -- The Hegelian development of Deweyan democracy -- The pursuit of democratic political institutions -- From deliberative to participatory democracy -- Agonism, communitarianism, and cosmopolitanism -- Educating democratic individuals -- Conclusion -- Bibliography
Title from publisher's bibliographic system (viewed on 09 Oct 2018)